The literature of the Iglesia Ni Cristo an annotated bibliography, 1914-1980 - Plopino, Luz F.; Covar, Prospero; Faderon, Rosalie B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1981)
The Iglesia ni Cristo (INC) is one of the many religious movements in the Philippines. The INC demonstrates unusual dynamism and power even in the secular affairs of Philippine society.
From its emergence in 1914 up to the present, a considerable number of articles, books, manuscripts and related literature have been written about it. The task at hand is an attempt to compile and annotate them.
The INC materials included here were gathered from a survey of various libraries and offices in the Metro Manila area. Published and unpublished indexes, theses abstracts, catalogs and bibliographies were checked. Likewise, books, pamphlets, manuscripts, periodical and newspaper articles were located and read in order that the researcher could provide the descriptive annotations.
A total of 429 entries are cited and annotated in this bibliography. These are grouped into four broad subject headings: General, Doctrines, History, and Organization. Each of these, except the first one, is further subdivided and under each subheading are the relevant entries arranged alphabetically by author and/or title.
The first subject category, General, includes those works which give an overview of the various aspects of the INC: history, organization, indigeneity, membership and propagation. Thereunder, the entries are arranged alphabetically by author/title.
The second category, Doctrines, is subdivided into the different doctrines of the INC: the Bible--the Sole Basis of INC Doctrines, Belief in One God, Christ's True State of Being, True Church, Salvation, Apostasy, Reestablishment of the Church of Christ, Felix Manalo: God's Last Messenger, Baptism by Immersion, Worship Service, Unity, INC Builds Houses of Worship, Missionary Work, Eating of Blood Forbidden, INC Prohibits Marriage with Non-Believers, Contributions, and Judgment Day.
The third subject category, History, includes those works which trace the growth and development of the INC since 1914. Subdivisions under this category include Local Congregations, Foreign Congregations, Leaders and Converts. Works categorized under each of these lay emphasis on the history of the pertinent subdivision.
The fourth and last category, Organization, includes work which focus on the organizational structure, ministry, functions, membership, and various activities of the INC. Subdivisions for this category are: Membership, Ministry, Chapels, Official Publication, Associations, Role of Foreign Congregations, Secular and Religious Activities. The last two are further subdivided into: Politics, Community Involvement, Labor and Debates, Sunday School Hymns, Choirs, Church Anniversaries, respectively.
Mimeographed.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Iglesia Ni Cristo -- Bibliography